First deceased by covid-19 in Peru - Cáceres-Bernaola, Ursula (2020)
The case of the first deceased in Peru is presented. 78-year-old man, with a history of hypertension, who presented a characteristic clinical picture of the disease caused by the new coronavirus (COVID-19), which had fundamental epidemiological data, the positive confirmatory test together with some laboratory parameters and radiological image also characteristic; that followed a fatal evolution, despite receiving the recommended therapy at that time. This case highlighted the need to quickly identify those patients who could have an unfavorable evolution, in order to provide the earliest and most adequate treatment.